APPLICATION OF INFORMATION TECHNOLOGY IN PHYSICS LESSON DURING LABORATORY WORKS IN SECONDARY SCHOOLS: ПРИМЕНЕНИЕ ИНФОРМАЦИОННЫХ ТЕХНОЛОГИЙ НА УРОКАХ ФИЗИКИ ПРИ ВЫПОЛНЕНИИ ЛАБОРАТОРНЫХ РАБОТ В СРЕДНИХ ШКОЛАХ. (Scientific journal of the Fergana State University, 2026)
This article examines what information technologies are used in physics laboratory workshops and how they affect learning. They emphasize its importance in communicating new knowledge to students, in developing students' intelligence, in shaping their perception and formulating conclusions.